Simple and cost-effective 14-loci SNP assay designed for differentiation of European, East Asian and African samples. (January 2015) - Rogalla, Urszula; Rychlicka, Edyta; Derenko, Miroslava V.; Malyarchuk, Boris A.; Grzybowski, Tomasz
Highlights: 14 SNPs easily differentiate Europeans, East Asians and Africans. Assays' discrimination performance is dependent on availability of reference samples. Siberians differ significantly in proportion of admixture pattern. Abstract: During every criminal investigation, it is vital to extract as much information as possible from every piece of evidence. When it comes to DNA testing, simple short tandem repeat (STR) typing may soon become a relic because it is now possible to genotype more characteristics. Ancestry informative markers are receiving attention from the forensic community because individuals can be assigned to their population or territory of origin based on their analysis. Many panels of this kind have been proposed so far, yet most of them require typing of a large number of loci. In many cases it is crucial to pick a minimal set of the most informative markers due to the limited amount of material available for analysis. In this study, we demonstrate that 14 carefully picked SNPs combined in two multiplex assays are capable of fast, robust and cost effective three-way differentiation of East Asians, Europeans and Africans.